Does Disruptive Event Affect Supply Base Size: Evidence from an Emerging Economy. Issue 4 (November 2020) - Pant, Pushpesh; Vishal, Hari; Sarmah, S. P.
This article examines the effect of disruptive event, namely recession, on supply base management (measured by supply base size) by using a large and longitudinal dataset on Indian manufacturing firms. It is found that the buyer firms have increased their supply base size at the annual rate of 8.23 suppliers per year per manufacturer during the pre-recession (2004–2007) period. The strategy of having a larger supply base is viable, specifically, in an emerging economy (e.g., India) as the probability of disruptions is high due to the inadequacy of basic inputs such as physical infrastructure, logistics services, technology, etc. Therefore, manufacturers tend to have a number of suppliers for the same product group to reduce supplier dependence. Further, we find that buying firms preferred to have a larger supply base even after a recession (2010–2013). However, they have increased their supply base size at the annual rate of just 0.2 (compared to 8.3 during the pre-recession period) suppliers per year per manufacturer during the post-recession. This study highlights the importance of a disruptive event (proxied by recession), by examining its association with supply base size in the emerging economy perspective. JEL Codes: C1, C5, C8